2021
DOI: 10.1016/j.imr.2021.100749
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and herbal supplements for fatigue: A quality assessment of online consumer health information

Abstract: Background The Internet is increasingly utilized by patients to acquire information about dietary and herbal supplements (DHSs). Previously published studies assessing the quality of websites providing consumer health information about DHSs have been found to contain inaccuracies and misinformation that may compromise patient safety.. The present study assessed the quality of online DHSs consumer health information for fatigue. Methods Six unique search terms were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In addition, advertisement-included videos had significantly lower DISCERN and GQS scores. Consistently, several studies have reported that the information available on commercial websites for dietary and herbal supplements is largely poor quality compared with health portal websites [ 31 , 70 ]. Similar to these studies, Gkouskou et al declared that commercial websites had a significantly lower reliability score than institutional and other websites [ 71 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, advertisement-included videos had significantly lower DISCERN and GQS scores. Consistently, several studies have reported that the information available on commercial websites for dietary and herbal supplements is largely poor quality compared with health portal websites [ 31 , 70 ]. Similar to these studies, Gkouskou et al declared that commercial websites had a significantly lower reliability score than institutional and other websites [ 71 ].…”
Section: Discussionmentioning
confidence: 95%
“…This situation limits the comparison of DISCERN, JAMA, and GQS scores with similar studies. However, there are a few studies that analyzed the DISCERN scores of online resources regarding herbal supplements, sports medicine, and nutrition [ 31 , 70 , 71 , 72 , 73 ]. For instance, Ng et al showed that online resources containing complementary and alternative-medicine-specific information vary in quality, according to the DISCERN instrument [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fatigue–physical activity association is multifactorial, which can be explained by body composition, physical fitness, and comorbidity [ 15 ]. Thus, the vulnerability to fatigue from PA could be dependent on nutritional supplements with antioxidant properties, which may contribute to the severity of the fatigue [ 16 , 17 ]. It is known that minerals and vitamins are essentials to avoiding fatigue and loss of energy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using articles and books published in popular media outlets as a proxy, we can observe that kratom is now being advertised and sought out as a performance-boosting ("nootropic") or wellness supplement (Mun and Wong, 2020;Carcache de Blanco and Kinghorn, 2021;Ng et al, 2021). A recent content analysis of over 42,000 comments made on kratom-related YouTube videos found that 50% reported use of kratom for its energy-boosting effects and 25% for its purported nootropic effects (Prevete et al, 2021).…”
Section: Kratom's Relevance To Rural Regionsmentioning
confidence: 99%